Internalisasi Nilai Nasionalisme dalam Aktivitas Sehari-Hari Generasi Muda Indonesia - Hanum Zatza Istiqomah; Clara Oda Oktavernanza; Anisa Sulis Saputri; Muhamad Fachry Zacky; Sylviatul Muthqia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The weakening of nationalism among the younger generation, especially Generation Z, has become a strategic issue amid the enormous influence of digital globalization. This generation grew up in a fast-paced and connected technological ecosistem (digital natives), which makes them vulnerable to foreign cultural domination and prone to referring to external values in their daily lives. This article aims to examine the process of internalizing nationalist values in the daily lives of Indonesia's young generation and formulate strategies to strengthen national values relevant to the digital era. This study employs a descriptive qualitative approach based on a literature review, analyzing various scientific literature and current digital sources. Data were collected from academic literature, journals, and relevant digital sources. The main findings show that nationalism is not only reflected in national symbols but also in concrete actions such as loving local products, participating in community activities, and using social media wisely to voice concern for the nation. On the other hand, the main challenges faced are low critical digital literacy and transnational information flows that have the potential to erode national identity. Therefore, the internalization of nationalist values requires an interdisciplinary, participatory, and contextual approach through meaningful social experiences for the younger generation.